Situating Breastfeeding within Development in the Philippines - Acielo, Johanna Marie Astrid E. (Review of Women's Studies; Vol 24 No 1-2 (2014): Review of Women's Studies Volume XXIV, Numbers 1-2 (January-December 2014), 2023)
While I believe that breastfeeding is a beneficial biosocial practice in any society, the politics within which it is entrenched in today's world need to be critically analyzed. As it is a practice that has lost its dominance in a world governed by neoliberal market forces and globalist development discourse surrounding child-rearing and nutrition, there is a dearth of literature exploring its connection to the problematique of modern-day development and its relation to specific women and their bodies. This paper situates the decline of breastfeeding with the historical, economic, and political conditions of neo-globalization, leading its inclusion in the larger discourse of development. Over the years, breastfeeding was touted as a means of population control and a solution for child malnutrition. These agendas have been re-articulated in national policy but are devoid of the underlying gender and class issues, generalizing women's bodies and breasts as apolitical entities and as sites of reproductive and productive imperialism (Kuumba, 1999).